Children’s Opinion on Vegetables Consumption: A Qualitative Study on School-Agers in City of Semarang - Natalia Ratna Yulianti; Eka Wahyuningrum; Andri Kenti Gayatina; Meira Erawati (Indonesian Journal of Applied Research (IJAR), 2021)
(1) Background: It Is recommended that children consume adequate amount of vegetables. However, the problem still remained in every single family and community. Many studies to find out its causes have been done. Unfortunately, most of them were conducted on parents only. Little is known from children’s own perspective. Children’s perspective is important to help adults in choosing vegetables for the children. Thus, this study aimed to explore children’s opinion on vegetables consumption.; (2) Methods: Qualitative design was employed. Samples were selected using purposive technique sampling. Nine participants aged 6-12 years were interviewed in a focus group discussion. Data were analysed using qualitative data analysis by Miles and Huberman.; (3) Results: The FGD indicates three themes: why kids dislike vegetables, sort of vegetables which kids love to consume, reasons why kids want to eat vegetables.; (4) Conclusions: Health education and involving children in their own food preparation is promising way to improve vegetables intake. Further research is to develop a new form of health education and a program in which children are involved to choose and prepare their own vegetables.